USING VISUAL MEDIA IN TEACHING SPEAKING - Ahmad Baidawi (IAIN MADURA, 2016)
Speaking is considered the most important skill of language especially English because having ability to speak is one of the evidence that someone has good proficiency of the language itself. Therefore, it is very urgent to teach speaking to the students in order that they master it well. To teach speaking, the teacher must design learning activities as well as possible and it also must be supported by various teaching media especially visual media such as pictures, realia, television etc. in order that learning activities is more various, interesting and motivates students to participate actively. The presence of visual media presents different learning experience which can stimulate students to think creatively so that they always get new idea to express when they want to speak. Therefore, the more various the teacher uses the media, the better learning objectives students achieve